1998
DOI: 10.1001/jama.279.8.609
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcome Following Maternal Use of the New Selective Serotonin Reuptake Inhibitors

Abstract: Context.-Although a large number of women of reproductive age use new selective serotonin reuptake inhibitors (SSRIs) and half of all pregnancies are unplanned, no data exist on the safety of these agents for the human fetus. Objective.-To assess fetal safety and risk of fluvoxamine, paroxetine, and sertraline. Design.-A prospective, multicenter, controlled cohort study. Setting.-Nine Teratology Information Service centers in the United States and Canada. Patients.-All women who were counseled during pregnancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
160
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 374 publications
(164 citation statements)
references
References 9 publications
2
160
0
2
Order By: Relevance
“…In the current study, patients with a wide spectrum of illness severity, including those with highly recurrent illness, elected to discontinue antidepressants during pregnancy frequently to avoid fetal exposure to these medications. That patients with even highly recurrent illness elected to discontinue antidepressant therapy is not surprising given concerns about prenatal exposure to medications, particularly when only sparse data regarding risks of fetal exposure are available for some of the most widely used antidepressants [5, 8]. Nonetheless, nearly half the sample (42%) reintroduced treatment with these agents, including those with and without multiple recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, patients with a wide spectrum of illness severity, including those with highly recurrent illness, elected to discontinue antidepressants during pregnancy frequently to avoid fetal exposure to these medications. That patients with even highly recurrent illness elected to discontinue antidepressant therapy is not surprising given concerns about prenatal exposure to medications, particularly when only sparse data regarding risks of fetal exposure are available for some of the most widely used antidepressants [5, 8]. Nonetheless, nearly half the sample (42%) reintroduced treatment with these agents, including those with and without multiple recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…These medications are considered to be safe during pregnancy due to their large therapeutic range and fewer adverse effects in comparison to other antidepressant medications [1,2,3]. …”
Section: Introductionmentioning
confidence: 99%
“…However, not all studies are in agreement,89,90,92,100,166,167 and one study even documented a reduced risk of spontaneous preterm birth associated with medication treatment of depressive symptoms during pregnancy, although the main exposure group included both sedative medications and antidepressants 32. Most studies to date have focused on antenatal SSRI use; however, an increased risk of preterm delivery has also been reported for TCAs, venlafaxine, and mirtazapine 97,127,128…”
Section: Resultsmentioning
confidence: 96%
“…The majority of individual studies have not demonstrated increased risk of MCMs associated with antidepressant exposure in the first trimester or at any time during pregnancy 87,89,92–104. Meta-analyses of studies investigating the risk of antidepressants and “any” or “overall” MCMs have shown either small but statistically significant risk105,106 or absence of significant increase in risk (Table 2).…”
Section: Resultsmentioning
confidence: 99%